Perspektif Kawasan dalam Studi Sejarah Islam: Menggali Dinamika Umat Islam dalam Konteks Kawasan - Asep Saefullah (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2012)
This article is based on review on Sejarah Kawasan Dunia Islam, by Ajid Thohir. The book summarizes the reality of the Islamic World in the real context of Islamic society. It can provide early recognition for whom study Islam in different regions. The study of it is becoming more and more interesting when looking at each geo-political region faced global accumulation, how they raise local ideology and establish the boundaries of geo-politics and geography, as well as identity and modernity. The study of Islamic history reveals various aspects of the life of Muslim communities in the local context necessitates a fair view of the Muslim community at the site concerned, but again shows the diversity in unity.